INCIDENCE OF METALLO-β-LACTAMASE (MBL) PRODUCING NONFERMENTERS ISOLATED FROM RESPIRATORY SAMPLES IN ICU PATIENTS - VEENU GUPTA; DEEPINDER CHHINA; AMARJEET KAUR. (International Journal of Pharma and Bio Sciences, 2013)
Nonfermenting gram negative bacilli (NFGNB) cause serious infections in immuncompromised and hospitalized patients. They cause fatal lower respiratory tract infections in patients admitted to ICU’s. The appearance of metallo ß-lactamases (MBL) genes and their spread among bacterial pathogens is a matter of concern. The present study was undertaken to know the prevalence of MBL producing NFGNB.NFGNB isolated from respiratory samples of patients admitted in various ICU’s were identified. The antimicrobial susceptibility testing was done as per CLSI guidelines.. Imipenem resistant isolates were selected for the detection of MBL production by Imipenem-EDTA combined disc test. A total of 445 NFGNB were isolated, Acinetobacter baumannii was the most common isolate followed by Pseudomonas aeruginosa. Piperacillin/tazobactam and imipenem were the most effective antibiotics. 40 % of A. baumannni and 20% of P.aeruginosa isolates showed resistance to imipenem. MBL production was detected in 80.1% isolates. To conclude, carbapenem resistance and MBL production in NFGNB is not uncommon.